1982
DOI: 10.1021/jo00146a031
|View full text |Cite
|
Sign up to set email alerts
|

Polar substituent effects in 1,3-disubstituted bicyclo[1.1.1]pentanes

Abstract: The pAa's of eight 3-substituted bicyclo [1.1.1] pentanecarboxylic acids have been measured and found to correlate well with constants. The value of (2.23 ± 0.12) is large but not large enough to propose any special perturbation of normal field-inductive effects by the close proximity (about 1.88 Á) of the bridgehead carbons. Also determined were the products and rates of solvolyses of the p-nitrobenzoates of three 3-substituted l-(2-hydroxy-2propyl)bicyclo [1.1.1] pentanes. The products were primarily unrearr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 0 publications
2
76
0
Order By: Relevance
“…This involved a new five‐step synthetic route from commercially available starting materials with an overall yield of 32 %. This is an improvement over the original seven‐step synthesis which had a yield of 14 % and incorporated the use of the corrosive hydrazoic acid reagent . The key step involved a novel, potentially versatile method using metal‐free homolytic alkylation.…”
Section: Application Of Rigid‐linear Linkers In Small Molecule Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…This involved a new five‐step synthetic route from commercially available starting materials with an overall yield of 32 %. This is an improvement over the original seven‐step synthesis which had a yield of 14 % and incorporated the use of the corrosive hydrazoic acid reagent . The key step involved a novel, potentially versatile method using metal‐free homolytic alkylation.…”
Section: Application Of Rigid‐linear Linkers In Small Molecule Drugsmentioning
confidence: 99%
“…This is an improvement over the originals evenstep synthesisw hichh ad ay ield of 14 %a nd incorporated the use of the corrosive hydrazoic acid reagent. [341] The key step involved an ovel,p otentially versatile methodu sing metal-free homolytic alkylation.…”
Section: Reviewmentioning
confidence: 99%
“…The pK a of anilinei s4 .6;i ti ncreases to 8.6 for BCP-NH 2, [21] and to 10.7 for BCO-NH 2. [22] While pK a values are not statistically correlated to CHI(IAM), when all else remains equal, basicity influences NSB [7,23] and para-substituted anilines are expected to have lower CHI(IAM) values than the corresponding bicycloalkylamines. Accordingly,adrug-like molecule (K,T able 2) showed an increase in CHI(IAM) value of + 8.9 units upon replacemento ft he p-Ph-NH 2 group by BCP-NH 2 .…”
Section: Effect Of Ionizable Groupsmentioning
confidence: 99%
“…[1] [2] the once tedious syn-revealed that this reaction most probably proceeds by a radthesis of the parent bicyclo[1.1.1]pentane (3) [3] and its de-ical chain mechanism and requires careful choice of solvent rivatives [4] has been greatly simplified. 1,3-Disubstituted bi-and reaction conditions.…”
Section: Resultsmentioning
confidence: 99%